Left atrial conduit flow rate at baseline and during exercise: an index of impaired relaxation in patients with heart failure and preserved ejection fraction. (14th October 2021) - Marino, P; Zanaboni, J; Degiovanni, A; Patti, G; Fraser, A
Abstract: Introduction: In healthy subjects, adrenergic stimulation augments left ventricular (LV) long-axis shortening/lengthening, and increases left atrial (LA) to LV intracavitary pressure gradients in early diastole. Lower increments are observed in patients with heart failure with preserved ejection fraction (HFpEF). Purpose: We hypothesized that exercise in HFpEF would similarly impair passive LV filling in early-mid diastole, during conduit flow from pulmonary veins. Methods: Twenty HFpEF patients (67.8±9.8 years; 11 women), diagnosed according to 2007 ESC recommendations, underwent ramped semi-supine bicycle exercise to submaximal target heart rate (∼100) or symptoms. Seventeen asymptomatic subjects (64.3±8.9 years; 7 women) served as controls. Simultaneous LA and LV volumes were measured from pyramidal 3D echocardiographic full-volume datasets acquired from apical window at baseline and during stress, together with brachial arterial pressure. LA conduit function was computed, from minimum LV volume to ECG P wave, as [LV volume (time) – LV minimum volume] – [LA maximum volume – LA volume (time)] and expressed as average flow rate. The slope of the single-beat preload recruitable stroke work (PRSW) quantified LV inotropic state. Results: There were divergent responses in conduit flow rate, which increased by 40% during exercise in control subjects (+17.8±37.3 ml/s) but decreased by 18% in patients with HFpEF (−9.6±42.3 ml/s) (p=0.046); increments during stress correlated with PRSW slope changes (p=0.003). Conclusion: In HFpEF conduit flow rate decreases when diastolic dysfunction develops during exercise, in parallel with LV inotropic state changes, thereby contributing to impaired stroke volume reserve. Conduit flow can be measured as a marker of LV relaxation. Funding Acknowledgement: Type of funding sources: None.